2009
DOI: 10.1111/j.1460-9568.2009.06866.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of motor patterns by the central spike‐initiation zone of a sensory neuron

Abstract: Sensory feedback from muscles and peripheral sensors acts to initiate, tune or reshape motor activity according to the state of the body. Yet, sensory neurons often show low levels of activity even in the absence of sensory input. Here we examine the functional role of spontaneous low-frequency activity of such a sensory neuron. The anterior gastric receptor (AGR) is a muscle tendon organ in the crab stomatogastric nervous system whose phasic activity shapes the well-characterized gastric mill (chewing) and py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 52 publications
6
62
0
Order By: Relevance
“…Our findings support the conclusion of Daur et al [23] in that axonal modulation not only occurs spontaneously, but is reliably present when gastric mill rhythms are elicited. While changes in AGR firing frequency had been observed, they had never been correlated to the motor pattern before.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings support the conclusion of Daur et al [23] in that axonal modulation not only occurs spontaneously, but is reliably present when gastric mill rhythms are elicited. While changes in AGR firing frequency had been observed, they had never been correlated to the motor pattern before.…”
Section: Discussionsupporting
confidence: 92%
“…Perhaps a discussion in that context would be useful (e.g. Daur, Nadim and Stein, 2009 . European Journal of Neuroscience, Vol.…”
mentioning
confidence: 99%
“…It begins to fire two independent spikes (instead of a single, tonic spike), one of which propagates through the son, stn, and dgn that appears to originate in the stn, whereas a second independent spike propagates only in the dgn in our recordings (Fig. 5, 72-h block, far right; see also Daur et al 2009). …”
Section: Resultsmentioning
confidence: 68%
“…These effects do not seem to simply be due to damage of the descending stn fibers. Using AGR activity as a monitor of stn propagation ability (Daur et al 2009), we found no significant differences in AGR spike propagation ability over time in both control and sucrose preparations, indicating the propagation ability of the stn is likely maintained throughout these experiments.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation